Hubungan Fungsional Desa Pakraman dengan Desa Dinas dalam Pelaksanaan Pembangunan di Desa Pererenan Menurut UU No. 6 Tahun 2014 - I Made Restu Putra; I Wayan Arthanaya; Luh Putu Suryani (Warmadewa Press, 2020)
Indonesian Constitution No. 6 of 2014 concerning Villages stipulates that a village refers to official village and traditional villages, but hereinafter referred to as village. This implies that there is a village government organizer. If this provision is applied in Bali, however, it will trigger an indication of the blurring of norms since in Bali there are two types of villages, namely Desa Pakraman (customary village) and official village, and the same is true in Desa Pererenan. The official village carries out the function of administering government administration and the Desa Pakraman (customary village) carries out the function of administering customary and religious affairs. The dualism of governance in villages in Bali, including in Pererenan Village, in the implementation of village development, can cause problems, because each village has autonomous rights in carrying out government functions. Therefore, this study highlights two things, namely how the development is planned in Desa Pererenan and the functional relationship between the Desa Pakraman and the official village in the implementation of development. The method used to examine these two issues is the normative research method, which involves qualitatively analyzed documents, both official and in the form of notes, laws and regulations and related government regulations. The research conclusions are drawn deductively. Based on the results of data analysis, it can is revealed that the development planning process (physical and non-physical) in Desa Pererenan refers to the Badung Regency development planning pattern, such as the National Plan of Development Plan (PPNSB), which adopts the philosophy of life and local wisdom of the Balinese people. Village development planning involves the Village Consultative Body (BPD) and the community in a participatory manner, is compiled in a periodic manner, and includes the Village Medium-Term Development Plan (RPJM) for a period of 6 (six) years and the Village Government Work Plan (RKP) for a period of 1 ( one year). The relationship between the desa pakraman and the official village in Pererenan Village is functional, namely consultative and coordinative, which is the working relationship between the prajuru desa pakraman (head of desa pakraman) and the official or perbekel village head. The duties and authorities of the two villages have differences but are still interrelated with one another.